Guidelines for Effective Regulatory Consultations - Secrétariat du Conseil du Trésor du Canada (2007)
These guidelines are issued to advise managers and functional specialists on interpretation of the requirements of the Cabinet Directive on Streamlining Regulation regarding regulatory consultation and to provide tools to support effective consultations throughout the regulatory life cycle.